Gender and the Idea of Labour Law - Conaghan, Joanne (feminists@law, 2014)
In recent years and as a consequence of radical changes in the world of work the idea of labour law has come under sustained interrogation. Of particular concern has been the extent to which the traditional boundaries of labour law organised around the regulation of employer-employee relations are in need of revision, as the ambit of labour regulation expands outwards to encompass a much broader range of socio-economic and political objectives. Such developments, inter alia, present feminists with an opportunity to challenge the extent to which labour law is predicated upon a paid work paradigm and to emphasise the interconnectedness of paid and unpaid labour and the significance of gender as a category of analysis in this context. Taking as a particular focus a recent collection of essays entitled The Idea of Labour Law, edited by Guy Davidov and Brian Langille (OUP 2011), this paper endeavours to gauge how far mainstream labour law debate has taken up the feminist challenge to confront the implications - for labour regulation - of acknowledging the interdependence of work and family life and the constituting significance of gender in relation to the social (and legal) organisation of work.